The Characteristics of Sodium Alginate from Brown Seaweed Sargassum crassifolium with Different Filtering Tools - Ellya Sinurat; Retni Marliani (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Indonesia is the largest producer of seaweed in the world, one of the potential marine biological resources is the brown seaweed (Sargassum crassifolium) known as an alginate producer. Alginate extraction through demineralization stage, neutralization, extraction, filtration, precipitation and bleaching. Filtration stage is a very influential process on the quality of alginate produced. In this research, filtering using different tools screen vibrator and hydraulic filter press was conducted to characterize Na-alginate seaweed Sargassum crassifolium using both filter tools. Quality of sodium alginate (yield, viscosity, gel strength, syneresis, whiteness, moisture content, ash, and pH) was determined. The result showed that the viscosity, gel strength, syneresis, and whiteness of alginate obtained using filter press showed the best result. The yield of sodium alginate produced by filter press was 10.91±4.33%, with characteristics of viscosity 82.66±112.46 cP, gel strength 353.54±184.51 g/cm2, syneresis 2.99±0.55%, whiteness 60.53±9.09%, moisture content 13.31±0.77%, ash 26.69±0.82% and pH 6.05±0.57. Based on a parameter of alginate (yield, moisture content, ash, and pH) showed that vibrator method produced alginate with better characteristics. The sodium alginate produced has average yield 19.22±5.68%, viscosity 57.5±21.79 cP, whiteness 29.7±4.45%, gel strength 327.63±55.15 g/cm2, syneresis 4.34±0.78%, moisture content 10.23±1.68%, ash 24.94±4.41% and pH 7.03± 2.60. Operationally the filter press was more effective and efficient in filtering to result from Na-alginate compared to the screen vibrator.